Designing a Sandbox for Smarter Health Solutions - Bergman, Wilma; On Huang, Susanne (My University, 2025)
Efficient and accurate decision making is of high importance in emergency healthcare, particularly in the triage of traffic related incidents. However, current systems face challenges such as overtriage and limited use of available data. As a result, the Care@Distance team at Chalmers has developed the ASAP framework, which includes the development of a Digital Health Sandbox (DHS). This thesis centers on the creation of the DHS, a simulated environment designed to allow healthcare developers to test and explore triage related algorithms using synthetic data. It further explores how user-centered and visualization-focused design affect the usability of a digital interface aimed at improving healthcare planning and evaluation. Through an iterative design process grounded in User-Centered Visualization Design (UCVD), a high-fidelity prototype was developed and evaluated with input from end users. The prototype enables simulation visualizations of healthcare scenarios, with a focus on traffic accidents. The results suggest that user involvement and visualization techniques can improve the usability and clarity of digital tools intended for healthcare development. While the DHS remains a prototype, it offers insights into how design methodologies can help bridge the gap between technical solutions and user needs, contributing to the ongoing development of more effective and user adapted digital health tools.
Keywords: Sandbox; User-Centered Design; User-Centered Visualization Design; Usability; Information Visualization; Health Algorithms; Digital Health; Triage; Emergency Healthcare; Traffic Accidents